Analysis of herbicide atrazine and its degradation products in cereals by ultra-performance liquid chromatography-mass spectrometry. Issue 17 (20th April 2016) - Liang, Shuxuan; Dong, Xinfeng; Su, Ming; Sun, Hanwen
Abstract : A novel ultra-performance liquid chromatography-mass spectrometry (UPLC-MS) method was developed for the first time for the determination of herbicide atrazine (ATR) and its principal metabolites namely desisopropylatrazine (DIA), desethylatrazine (DEA) and hydroxyatrazine (HA) in cereals. Abstract : A novel ultra-performance liquid chromatography-mass spectrometry (UPLC-MS) method was developed for the first time for the determination of herbicide atrazine (ATR) and its principal metabolites namely desisopropylatrazine (DIA), desethylatrazine (DEA) and hydroxyatrazine (HA) in cereals. The limit of detection ranged from 0.06 μg kg −1 (DEA) to 0.25 μg kg −1 (HA). The intra- and inter-day relative standard deviations (RSDs) for the four analytes were 5.5–9.3% and 8.7–17.1% for cereal grain samples, respectively. Recoveries for the four targets at three spiked levels ranged from 71.9 to 106% with RSD of 3.1–8.1% for the cereals. The content of the analytes in cereals was determined as follows: 0.6–3.0 μg kg −1 for ATR and 0.6–1.6 μg kg −1 for DEA, while DIA and HA were not detected. The proposed method can ensure a rapid and highly sensitive analysis of atrazine and its degradation products in cereals, and can provide a direction for proper application of atrazine and a base for evaluating their hazards to food safety.